Anticancer Activity of Venom Protein Hydrolysis Fraction of Equatorial Spitting Cobra (Naja sumatrana) - Naseer Ahmed; Garnis Putri Erlista; Tri Joko Raharjo; Respati Tri Swasono; Slamet Raharjo (Universitas Gadjah Mada, 2023)
Bioactive peptides play an important role in targeting cancer cells. Venom protein from Naja sumatrana can be explored as a source of bioactive peptides. This research aims to identify and study the molecular docking of bioactive peptides (BPs) from trypsin hydrolysate of N. sumatrana venom protein which was fractionated using an SPE C18 column. The venom of N. sumatrana was hydrolyzed with trypsin enzyme. The protein hydrolysate was then fractionated using an RP-SPE HyperSep Retain PEP column, and the peptide fractions were tested for their anticancer activity against MCF-7 breast cancer cells using the (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. Identification of peptides in the active fraction was carried out through high-resolution mass spectrometry. The identified peptides were molecularly docked with the EGFR receptor using AutoDock Vina. The results showed that the degree of hydrolysis was 74.7%. The 75% methanol fraction is the active fraction against MCF-7 cells, with an IC50 value of 4.80 μg/mL and a selectivity index of 5.00. Peptide-active anticancer fractions with the sequence of NSLLVK, SSLLVK and TVPVKR were successfully identified and exhibited high binding affinity values, good RMSD values, and the most suitable model for the epidermal growth factor receptor.